2001
DOI: 10.1093/nar/29.17.e89
|View full text |Cite
|
Sign up to set email alerts
|

Linear 2' O-Methyl RNA probes for the visualization of RNA in living cells

Abstract: U1snRNA, U3snRNA, 28 S ribosomal RNA, poly(A) RNA and a specific messenger RNA were visualized in living cells with microinjected fluorochrome-labeled 2' O-Methyl oligoribonucleotides (2' OMe RNA). Antisense 2' OMe RNA probes showed fast hybridization kinetics, whereas conventional oligodeoxyribonucleotide (DNA) probes did not. The nuclear distributions of the signals in living cells were similar to those found in fixed cells, indicating specific hybridization. Cytoplasmic ribosomal RNA, poly(A) RNA and mRNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 49 publications
4
116
1
Order By: Relevance
“…1A). We chose 29-Omethyl RNA as the backbone of the probe, because this artificial nucleic acid is resistant to nucleases in living cells and it has a high affinity for nucleic acids (Molenaar et al, 2001;Okabe et al, 2011). The poly(U) 22 29-O-methyl RNA probe has previously been used to detect nuclear poly(A) + RNA (Molenaar et al, 2004;Ishihama et al, 2008).…”
Section: Endogenous Mrnas Visualized Using a Linear Antisense Probementioning
confidence: 99%
See 1 more Smart Citation
“…1A). We chose 29-Omethyl RNA as the backbone of the probe, because this artificial nucleic acid is resistant to nucleases in living cells and it has a high affinity for nucleic acids (Molenaar et al, 2001;Okabe et al, 2011). The poly(U) 22 29-O-methyl RNA probe has previously been used to detect nuclear poly(A) + RNA (Molenaar et al, 2004;Ishihama et al, 2008).…”
Section: Endogenous Mrnas Visualized Using a Linear Antisense Probementioning
confidence: 99%
“…To visualize endogenous mRNAs, we used a linear antisense 29-O-methyl RNA probe labeled with a fluorescent dye that can bind to native mRNA in a sequence-specific way (Molenaar et al, 2001;Molenaar et al, 2004;Ishihama et al, 2008;Okabe et al, 2011). A linear antisense probe was advantageous because of its ability to target native mRNA and its excellent hybridization kinetics in living cells (Okabe et al, 2011;Molenaar et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research described the tendency of molecular beacons to shuttle into the nucleus soon after they entered the cell. [15][16][17] In light of this, we identified the intron/exon boundaries in the mRNA and designed our target sequence to be contained only in the third exon. In anticipation of the beacon encountering mostly unprocessed RNA in the nucleus, a target sequence involving two adjacent exon sequences was avoided.…”
Section: Resultsmentioning
confidence: 99%
“…However, the long-term, real-time monitoring of viral RNA in living cells has not been possible because of the relatively short half-life (Ϸ30 min) of MBs due to endogenous nuclease degradation, resulting in false-positive signals (6,7). It has been shown that modifications of MBs with 2Ј-Omethyl RNA bases and phosphorothioate internucleotide linkages can be used to significantly improve duplex stability and nuclease resistance (8)(9)(10)(11)(12)(13). It is easy to envision that such an MB design can be adapted for the real-time monitoring of viral infection.…”
mentioning
confidence: 99%